Discovery of isoflavone phytoalexins in wheat reveals an alternative route to isoflavonoid biosynthesis - Guy Polturak; Rajesh Chandra Misra; Amr El-Demerdash; Charlotte Owen; Andrew Steed; Hannah P. McDonald; JiaoJiao Wang; Gerhard Saalbach; Carlo Martins; Laetitia Chartrain; Barrie Wilkinson; Paul Nicholson; et al. (Nature Communications, 2023)
Abstract Isoflavones are a group of phenolic compounds mostly restricted to plants of the legume family, where they mediate important interactions with plant-associated microbes, including in defense from pathogens and in nodulation. Their well-studied health promoting attributes have made them a prime target for metabolic engineering, both for bioproduction of isoflavones as high-value molecules, and in biofortification of food crops. A key gene in their biosynthesis, isoflavone synthase, was identified in legumes over two decades ago, but little is known about formation of isoflavones outside of this family. Here we identify a specialized wheat-specific isoflavone synthase, TaCYP71F53, which catalyzes a different reaction from the leguminous isoflavone synthases, thus revealing an alternative path to isoflavonoid biosynthesis and providing a non-transgenic route for engineering isoflavone production in wheat. TaCYP71F53 forms part of a biosynthetic gene cluster that produces a naringenin-derived O-methylated isoflavone, 5-hydroxy-2′,4′,7-trimethoxyisoflavone, triticein. Pathogen-induced production and in vitro antimicrobial activity of triticein suggest a defense-related role for this molecule in wheat. Genomic and metabolic analyses of wheat ancestral grasses further show that the triticein gene cluster was introduced into domesticated emmer wheat through natural hybridization ~9000 years ago, and encodes a pathogen-responsive metabolic pathway that is conserved in modern bread wheat varieties.